2015
DOI: 10.1039/c4cy00988f
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification processes during methane decomposition on Cu-promoted Ni–ZrO2catalysts

Abstract: We explored the surface chemistry of methane on Cu-promoted Ni–ZrO2 catalysts and observed a limited stability of the CuNi alloy under relevant reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 82 publications
2
39
0
Order By: Relevance
“…Also, reconstruction of the assynthesized catalytic structure under reaction conditions may be expected when significant adsorbate−metal specific interactions exist, for example in a CO atmosphere. 89 However, based on the lack of ring hydrogenation observed in our studies for the Cu−Ni/TiO 2 catalyst, it can be concluded that migration of Ni to the catalyst surface is minimal under reaction conditions.…”
Section: Discussionmentioning
confidence: 60%
“…Also, reconstruction of the assynthesized catalytic structure under reaction conditions may be expected when significant adsorbate−metal specific interactions exist, for example in a CO atmosphere. 89 However, based on the lack of ring hydrogenation observed in our studies for the Cu−Ni/TiO 2 catalyst, it can be concluded that migration of Ni to the catalyst surface is minimal under reaction conditions.…”
Section: Discussionmentioning
confidence: 60%
“…However, many researchers suggest that the Ni‐based catalysts also favor the CC cleavage, and the deposition of carbon, which is responsible for the rapid deactivation of the catalysts. Combining Ni with a second metal such as Cu was found to enhance not only the performances of the catalyst but also to improve carbon resistance . Besides, combining Ni with two other metals (Sn, K), also yielded improvement of the catalytic performances.…”
Section: Main Challenges and Perspectivesmentioning
confidence: 94%
“…Pd (111)Gabasch et al [129] Ethene oxidationPd(111)Gabasch et al [130] Methaned ecomposition Cu/Ni/ZrO 2 Wolfbeissere tal. [131] CO hydrogenationPd(111)Rupprechter et al [132] Methanol dehydrogenation Pd(111)Morkel et al [133]…”
Section: Methaneo Xidationmentioning
confidence: 99%